Demand management' and injustice in rural agricultural irrigation in western Colorado: an anatomy of ambivalence - MacIlroy, Kelsea E., author; Hempel, Lynn, advisor; Carolan, Michael, committee member; Malin, Stephanie, committee member; Kampf, Stephanie, committee member (Colorado State University. Libraries, 2022)
The Colorado River is overdrawn. Decisions made a century ago created an institutional framework allowing overuse while climate change has exacerbated it with increasing temperatures and reduced natural flows. 'Demand management', a key component of the 2019 Upper Basin Drought Contingency Plans, would utilize water conserved from consumptive use to create a 500,000 acre-foot storage pool, only used to protect the Upper Basin of the Colorado River in the event they were unable to meet water delivery obligation to the Lower Basin. Rural irrigators on Colorado's West Slope would be the prime contributors to such a program, but largely responded with ambivalence. Increasingly, collaborative water governance is cited as the best way to create change in water distribution. However, if rural irrigators respond with ambivalence, why would they participate voluntarily in such a program? Using a grounded theory approach, interviews and focus groups with 45 participants, and participant observation, I explore why rural irrigators were ambivalent towards a program that would, ostensibly, protect them in times of water shortage. Drawing from the concept of sociological ambivalence and the literatures of water justice, hydrosocial analysis, and rurality, I describe the symbolic and material landscape that shapes perceptions of 'demand management'. I argue irrigators were ambivalent because they understood the need for water conservation, but they also perceived injustice in terms of distribution, recognition, and representation. Since rural irrigators are the linchpin in any water conservation program that would address overuse in the Colorado River Basin, their perceptions of injustice must be addressed. Findings provide key insight into water governance as it relates to crafting effective water policy.
Demand management and injustice in rural agricultural irrigation in western Colorado: an anatomy of ambivalence
Keywords: Colorado River; irrigation; water justice; hydrosocial; agriculture; rural sociology